2021
DOI: 10.1017/erm.2021.19
|View full text |Cite
|
Sign up to set email alerts
|

Female fertility under the impact of COVID-19 pandemic: a narrative review

Abstract: Coronavirus disease 2019 (COVID-19) is a serious respiratory disease mediated by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. The worldwide spread of COVID-19 has caused millions of confirmed cases and morbidity, and the crisis has greatly affected global economy and daily life and changed our attitudes towards life. The reproductive system, as a potential target, is at a high risk of SARS-CoV-2 infection, and females are more vulnerable to viral infection compared with males. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 119 publications
0
10
0
Order By: Relevance
“…On a similar note, COVID-19 infection has also been associated with preeclampsia, preterm birth, and low birthweight in infants. It has been suggested that the effects of COVID-19 infection are likely associated with uteroplacental vasoconstriction and endothelial disfunction due to SARS-CoV-2 modulation of renin-angiotensin-aldosterone system by binding to angiotensin-converting enzyme 2 ( 53 , 54 ). The pathophysiology of uteroplacental blood perfusion and its impact on preterm birth under different scenarios such as SSRI use, gestational hypertension, preeclampsia, and COVID-19 needs to be addressed to improve maternal and fetal health.…”
Section: Discussionmentioning
confidence: 99%
“…On a similar note, COVID-19 infection has also been associated with preeclampsia, preterm birth, and low birthweight in infants. It has been suggested that the effects of COVID-19 infection are likely associated with uteroplacental vasoconstriction and endothelial disfunction due to SARS-CoV-2 modulation of renin-angiotensin-aldosterone system by binding to angiotensin-converting enzyme 2 ( 53 , 54 ). The pathophysiology of uteroplacental blood perfusion and its impact on preterm birth under different scenarios such as SSRI use, gestational hypertension, preeclampsia, and COVID-19 needs to be addressed to improve maternal and fetal health.…”
Section: Discussionmentioning
confidence: 99%
“…Bowman and his team studied the effect on BNT162b2 vaccine on female fertility in rats. They found that it has no impact on fertility, ovarian or uterine parameters and embryo-fetal development 26 . Moreover, another study by Devora Ahron et al, they compared early IVF outcomes between 28 patients who received Pfizer vaccine, 37 patients received the Moderna vaccine and 328 unvaccinated patients who were a control group.…”
Section: Introductionmentioning
confidence: 98%
“…The ACE2 has a vital role in endometrial proliferation and renewal. Accordingly, it is expected that the downregulation of ACE2 by SARS-CoV-2 could affect the endometrial stability and may impair implantation 22 26 . Whether this has a noxious effect on the endometrium due to COVID-19 infection or vaccination need to be clarified 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the ACE2 receptors are highly expressed in uterine, placental, and ovarian cells, there would be possible if COVID‐19 infection can affect fertility in women 13 . Although the effect of vaccination against COVID on fertility is still uncertain, but many studies revealed that vaccination would not affect ovarian reserve 14–16 . It is reported that vaccination can lead to short‐term menstrual alterations 11,17–19 …”
Section: Introductionmentioning
confidence: 99%
“…13 Although the effect of vaccination against COVID on fertility is still uncertain, but many studies revealed that vaccination would not affect ovarian reserve. [14][15][16] It is reported that vaccination can lead to short-term menstrual alterations. 11,[17][18][19] Anti-Müllerian hormone (AMH) is a glycoprotein produced by the ovarian preantral and small antral follicles which are known as a predictor of ovarian reserve estimation.…”
Section: Introductionmentioning
confidence: 99%